A Review of Ozone Systems Costs for Municipal Applications. Report by the Municipal Committee – IOA Pan American Group. (4th July 2018) - Mundy, Bill; Kuhnel, Ben; Hunter, Glenn; Jarnis, Robert; Funk, Denise; Walker, Susan; Burns, Nick; Drago, Joseph; Nezgod, William; Huang, Joseph; Rakness, Kerwin; Jasim, Saad; et al.
ABSTRACT: Ozone has proven effective in improving water treatment plant performance, increasing customer satisfaction, and meeting increasingly stringent regulatory requirements. The benefits include disinfection; reducing chlorine disinfection by-products; micro-coagulation; enhanced filter performance; biological filtration; oxidation of iron, manganese, sulfide, taste- and odor-causing compounds, pharmaceuticals and personal care products (PPCPs), and endocrine disrupting compounds (EDCs). Despite the effectiveness of ozone in water treatment, a perception remains that ozone may be too expensive for consideration at many water treatment facilities. This paper presents an evaluation by the Municipal Committee of the International Ozone Association (IOA-MC) that aims to provide a realistic assessment of the current capital and operating costs of ozone in the North American water treatment practice. A general strategy is proposed for developing preliminary estimates of ozone capital and operating costs that could be used by engineers and/or owners for planning purposes. The information presented may benefit utilities, managers, and engineers engaged in the evaluation of treatment options.